Living Near Wildfires and the Risk of Fetal Congenital Heart Defects: Evaluating Critical Windows of Vulnerability - Park, Bo Y.; Vedhanayagam, Kriti; Ortiz-Luis, Jared; Basu, Rupa; Gheorghe, Ciprian P.; Govindappagari, Shravya; Abinader, Ray; Yao, Ruofan (American Journal of Perinatology Reports, 2025)
Background Wildfires produce air pollutants that have been associated with complications during pregnancy. This study examined the association between wildfire exposure before and during pregnancy and the odds of congenital heart defect (CHD) in the offspring.Methods This retrospective cohort study used the California Linked Birth File and the Forestry and Fire Protection data between 2007 and 2010. Patients living within 15 miles of wildfire during pregnancy were considered exposed. Multivariate logistic regression models were used to estimate the association between wildfire exposure by these various exposure metrics and atrial septal defect (ASD) or ventricular septal defect (VSD) types of CHD compared to pregnancies without wildfire exposure.Results Compared to births without wildfire exposure, those with first-, second-, and third-trimester exposure were associated with a higher risk of ASD with a first-trimester adjusted odds ratio (aOR) of 1.11 (95% confidence interval (CI): 1.04–1.18), second-trimester aOR of 1.12 (95% CI: 1.07–1.18), and third-trimester aOR of 1.08 (95% CI: 1.02–1.14). Wildfire exposure during the critical window of fetal heart development (weeks 3–8) was associated with aOR of 1.12 (95% CI: 1.02–1.23).Conclusion Wildfire exposure during pregnancy appears to increase the risk of developing ASD.Key points
Keywords: wildfire; congenital heart defect; pregnancy; air pollution